FAKTOR–FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN PNEUMONIA PADA BALITA DI RUMAH SAKIT UMUM DAERAH (RSUD) KOTA PADANGSIDIMPUAN TAHUN 2020 - DEWI AMINASTY SIREGAR (JURNAL ILMIAH KOHESI, 2020)
Background : Health is a healthy, physical, mental, spiritual and social condition that enables everyone to live socially and economically productive. Toddlers are a nutritious age group and are prone to illness. Objective: To analyze Factors Associated with Pneumonia Occurrence in Toddlers At District General Hospital (RSUD) Kota Padangsidimpuan Year 2020. Method : This research use analytic survey design with cross sectional approach.The number of samples in this study were 65 respondents. Result : The result of chi-square test showed that there was a relationship of birth weight (p = 0,036), breastfeeding (0.006), basic immunization (0,022), asthma disease (0,004), and no vitamin A (p = 0,828) relationship with pneumonia incidence. Furthermore Binary Logistic test results show that there is influence of birth weight OR = 4,017, breastfeeding OR = 5,764, and Asthma OR = 5,529 with the incidence of pneumonia in infants at the Regional General Hospital (RSUD) Kota Padangsidimpuan 2020. Conclusion :To the Regional General Hospital (RSUD) Kota Padangsidimpuan to pay more attention and socialize factors associated with the incidence of pneumonia, especially in toddlers so as to maintain the body's cells so as not easily attacked by the disease especially pneumonia and reduce child mortality rate.